Smart Lighting System Design at STMIK AMIKOM Surakarta Using Blynk - Adristiawan, Ranu Arva; Widiati, Ina Sholihah; Sugiarto, Lilik (Journal of Artificial Intelligence and Software Engineering, 2025)
The Internet of Things (IoT) is a technology that enables automation in human activities by connecting hardware, software, and the internet for communication and control. This study focuses on an IoT-based smart light control system designed using the Blynk app. The system utilizes the ESP8266 NodeMCU module and a 5V 8-Channel Relay as the primary components. The Blynk app is used as the controller, connecting the hardware to the user through an Android device. The research follows an experimental approach with three phases: tool design, tool construction, and tool testing. A miniature of the STMIK AMIKOM SURAKARTA environment was used as a prototype to simulate the system’s implementation. Test results show that the system operates effectively in remote control with internet coverage of up to 30 meters, achieving a 100% success rate within a range of 5–30 meters. All lights responded correctly to input commands from the Blynk app with 100% success. The monitoring system also showed stable connectivity between the app and hardware, though slight delays occurred due to internet network stability. This system is expected to serve as a practical solution for efficient management of electrical devices in educational settings, improving both energy efficiency and convenience.